Measles outbreak in Nišava and Toplica Districts from 2017 to 2018 - Rančić, Nataša; Stojanović, Miodrag; Milenković, Nikola; Perović, Miodrag; Janićijević, Ivana; Kostić, Marina; Stojanović, Marko; Jovanović, Marko; Ignjatović, Aleksandra; Anđelković Apostolović, Marija (Acta medicae Medianae, 2021)
Abstract Introduction. Measles was the leading cause of death among children under 5 years of age before the introduction of obligatory vaccination. The objective of the paper was to describe the epidemiological and clinical characteristics of the affected in the large measles outbreak in 2017-2018 in the Nišava and Toplica Districts. Material and Methods Descriptive study was done. For the investigation of the outbreak, the general principles of the case definition of the European Union (EU) Commission Decision of 2012 were used. Laboratory investigations of initial patients were conducted at the Center for Control and Prevention of Diseases in the Institute of Public Health Niš, and all specimens were sent and were tested for anti-measles IgM/IgG antibodies in referent laboratory of the Institute of Virology, Vaccines and Sera "Torlak" in Belgrade Results A total of 1327 (584 in males and 743 in females) cases were reported since 23 November up to 28 July 2018, when it ends. The average age was 35 years ranged from <1 year to 70 years. The highest number of patients were in the age group 30-39 years old 510 (38.4%) and the lowest number was at the age group of 15-19 years old, 34 (2.6%). Infants represented 5.3% of all affected and children from primary schools accounted for 4.4% out of all affected. One-fourth of the outbreak cases 338 (25.5%) were unvaccinated. Only 37 (2.8%) patients had received two doses of the combined vaccine against measles, mumps, and rubella (MMR) and 50 (3.8%) received one dose. For the majority of affected, 902 (68.0%) cases vaccination status was unknown. Measles-related complications were registered in 962 (72.5%) patients. Complications were the most common in infants (92.9%) and among children 1-6 years of age (88.2%). Malnutrition was the most frequent complication (823 cases, 62.0%) followed by diarrhea (590 cases, 44.5%), pneumonia (122 cases, 9.2%) and encephalitis were reported in 1 case. Measles-related deaths in the observed outbreak were confirmed in four patients (all laboratory-confirmed, three unvaccinated and an immune compromised child). The case-fatality rate of 0.3 per 100 measles cases was determined. Conclusion. The probable causes of this large measles outbreak were insufficient vaccination and low vaccine coverage with MMR vaccine and accumulation of a high susceptible population. Four measles-related deaths were registered. Monitoring of the vaccination status, high vaccine coverage and effectiveness of MMR vaccine are essential for the prevention of measles outbreaks. Key words: measles, outbreak, vaccination status, vaccination coverage, complications,